2020
DOI: 10.7759/cureus.9328
|View full text |Cite
|
Sign up to set email alerts
|

The Attend Study: A Retrospective Observational Study of Emergency Department Attendances During the Early Stages of the COVID-19 Pandemic

Abstract: Introduction: The coronavirus disease-19 (COVID-19) pandemic was associated with a large reduction in the number of attendances at emergency departments (EDs) in March 2020 in the United Kingdom (UK). We sought to identify which patient groups attended EDs least. Methods: Single-centre before and after study. We used routine administrative data from March 2020 and compared this to a composite control of March 2019 and February 2020. Results: Mean daily attendance fell by 30% from 342 patients per day in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 9 publications
6
16
1
Order By: Relevance
“…Our finding of a reduction in presentations to the emergency department during the COVID-19 pandemic is consistent with both national and international trends [ 7 – 10 ]. This directly influences the number of orthopaedic injuries cases being managed (either operatively or non-operatively) during the pandemic.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our finding of a reduction in presentations to the emergency department during the COVID-19 pandemic is consistent with both national and international trends [ 7 – 10 ]. This directly influences the number of orthopaedic injuries cases being managed (either operatively or non-operatively) during the pandemic.…”
Section: Discussionsupporting
confidence: 86%
“…The reduction in orthopaedic injury referrals has several possible explanations. First, it may reflect travel restrictions and social curfews resulting in decreased exposure to physical injury [ 7 ]. Second, it may reflect a reduction in work-related injuries associated with more people working from home [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the reduction of the number of ED attendances is consistent with previous studies. The Attend Study compared the daily ED attendances before and during the pandemic and observed a reduction by 30% daily ED visits ( 34 ). Franchini et al described the impact of the COVID-19 outbreak on an urban major-hospital ED attendance in Italy and observed a reduction in ED attendance by 37% ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with all outbreaks, the Emergency Department (ED) has been the primary portal of entry into hospitals for COVID-19 patients [3][4][5] . Despite the surge in suspected COVID-19 cases, there is global evidence to show that the Emergency Department (ED)'s overall daily attendance has declined [6][7][8][9][10][11] . Several studies have reported signi cant reductions in visits associated with time-sensitive and life-threatening conditions such as acute myocardial infarction and stroke [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%